Взрыв и время - Ужаревич, Йосип (SlavVaria, 2022)
Explosion and Time. The article discusses the interrelations between an ex-plosion and time in the latest books by Yuri Lotman. The composition of the article is based on two initial perspectives: one focuses on time in an explosion (present tense), and the second focuses on an explosion in time (past and future tense, history). Modern theory is unable to logically connect the explosion it-self with the phase immediately preceding the explosion, as well as with the phase that follows immediately after the explosion.